If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(0.5x + -8) + 9(x + -3) = 12 Reorder the terms: 2(-8 + 0.5x) + 9(x + -3) = 12 (-8 * 2 + 0.5x * 2) + 9(x + -3) = 12 (-16 + 1x) + 9(x + -3) = 12 Reorder the terms: -16 + 1x + 9(-3 + x) = 12 -16 + 1x + (-3 * 9 + x * 9) = 12 -16 + 1x + (-27 + 9x) = 12 Reorder the terms: -16 + -27 + 1x + 9x = 12 Combine like terms: -16 + -27 = -43 -43 + 1x + 9x = 12 Combine like terms: 1x + 9x = 10x -43 + 10x = 12 Solving -43 + 10x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '43' to each side of the equation. -43 + 43 + 10x = 12 + 43 Combine like terms: -43 + 43 = 0 0 + 10x = 12 + 43 10x = 12 + 43 Combine like terms: 12 + 43 = 55 10x = 55 Divide each side by '10'. x = 5.5 Simplifying x = 5.5
| 5x^2-50x+45=0 | | 0.6g+11=15 | | 10+5x=54+x | | 2r^2-10r-100=0 | | .2(x-25.5)+.3=.2(x-16) | | 12(y-1)=3(2x-4) | | x^2+4x=6 | | 3y^3+9y^2-162y=0 | | 3y+5y=8 | | x+(x+2)+(x+4)=48 | | 3(y+1)=6 | | 6x+78=12x+12 | | 3y^3+9y^2-162x=0 | | (a^2+1)a^2-7(a^2+1)=0 | | 64-y=2y+6 | | 7x^2+35x-168=0 | | x^2-16x+58=0 | | 6x+6y=12 | | 6x+38=16x-52 | | x^2-16x+64=6 | | y+5=-(x-2) | | 12x^2+9=24x | | 5(d-45)=4(d-30)+10 | | 2x^3-10x^2-100x=0 | | 5(1-2w)+8=15 | | 92-34=42-9 | | 92-34=4z-9 | | 10x+7=8x-11 | | 6c^3-3c^2-45c=0 | | 3d^2-2d-33=0 | | 6n^2+1-n+5n^2= | | 2c-15=36 |